Childhood Emotional Maltreatment and Post-Traumatic Stress Disorder in the Context of Centrality of the Event and Intrusive Rumination. (January 2021) - Watts, Justin; Leeman, Michael; O'Sullivan, Deirdre; Castleberry, Joshua; Baniya, Ganesh
Psychiatric disorders, such as post-traumatic stress disorder (PTSD), are significantly more likely among those exposed to child maltreatment. Not all who are exposed to maltreatment develop PTSD; while many contributing factors are understood, more research is needed to understand why some develop this disorder. The purpose of this study was to examine relationships among an understudied form of maltreatment: childhood emotional maltreatment (CEM) and cognitive processes that may directly or indirectly explain development of PTSD among CEM survivors. A sample of college students ( N = 396) completed surveys related to childhood trauma history, cognitive processing, and PTSD. Mediation analyses revealed that CEM had a significant direct effect on PTSD, and that centrality of the event and intrusive rumination significantly mediated this relationship. Recommendations are provided for identifying maladaptive cognitive processes with the aim of facilitating adaptive cognitive processing related to prior trauma exposure and current PTSD symptoms.